2017
DOI: 10.1016/j.jtcvs.2016.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy after esophagectomy: Safety demonstrated in a porcine model

Abstract: Endoscopy after esophagectomy with gentle or maximal air insufflation results in safe endoluminal pressures and minimal disturbance of blood flow and oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…15,16 Raman et al reported that endoscopy after esophagectomy with gentle or maximal air insufflation is safe in a porcine model, and endoscopy intervention does not mechanically disrupt the anastomosis or disturb blood flow and oxygenation. 17 Combining the results of our study, we conclude that early endoscopy intervention may be both feasible and safe.…”
Section: Discussionsupporting
confidence: 69%
“…15,16 Raman et al reported that endoscopy after esophagectomy with gentle or maximal air insufflation is safe in a porcine model, and endoscopy intervention does not mechanically disrupt the anastomosis or disturb blood flow and oxygenation. 17 Combining the results of our study, we conclude that early endoscopy intervention may be both feasible and safe.…”
Section: Discussionsupporting
confidence: 69%
“…Endoscopic air insufflation should always be gentle and progressive but even with maximum insufflation the intraluminal pressure at the anastomosis never increases beyond 9 cm H 2 O, with minimal disturbance of the blood flow in the conduit. 41 Clinical studies have confirmed that upper endoscopy performed within 1 week after esophagectomy is safe and can be performed at the bedside, even in a patient who is intubated, 12,42 without worsening an already existing leak. 20 The sensitivity of endoscopy is relatively high not only to assess the anastomosis but also to identify any degree of alteration of the integrity of the conduit, from mucosal ischemia to necrosis, and to provide information about the vitality of the gastric conduit.…”
Section: Upper Endoscopymentioning
confidence: 93%
“…Recent studies in an in vivo porcine model demonstrated that intraluminal pressure greater than 80 cm H 2 O is needed to disrupt an esophagogastric anastomosis. Endoscopic air insufflation should always be gentle and progressive but even with maximum insufflation the intraluminal pressure at the anastomosis never increases beyond 9 cm H 2 O, with minimal disturbance of the blood flow in the conduit …”
Section: Diagnosis Of Anastomotic Leak and Fistulamentioning
confidence: 99%
“…Endoscopy in this setting should be performed by an experienced endoscopist, and only gentle and progressive insufflation should be used. In their porcine studies, Raman and colleagues [17] were able to demonstrate that even at maximal insufflation, the anastomotic endoluminal pressure did not exceed 8.7 cm H 2 O pressure, which is far below what is needed to disrupt anastomosis or disturb tissue perfusion. The theoretical risk of further disruption of the anastomosis is a valid concern but should be weighed against the benefits of endoscopy in a patient with a suspected anastomotic leak.…”
Section: Diagnostic Work-upmentioning
confidence: 96%